ANALISIS KEBIJAKAN KREDIT TERHADAP PENGEMBANGAN USAHA PERIKANAN NELAYAN TRADISIONAL DI KABUPATEN TOJO UNA-UNA - Dewi Nur Asih (Universitas Tadulako, 2008)
Credit aid programs can be used as a mean to improve the contribution of fishery sector. The impact of such credit on traditional fisheries was determined on the fishery productivity and their traditional fisherman income in Sulawesi Tengah Province. The research result showed that the credit was needed as an additional capital for the fishery sustainability. With such credit, the productivity of the fisheries increased as shown by sufficiently high incremental benefit which the fishermen achieved. The credit also affected the fisherman household in making decision related to such economic behaviors as productivity activities, working time, income and expenditure. Thus these behaviors were analyzed using an econometric approach with a simultaneous equation.